Dampak penyuluhan kesehatan terhadap peningkatan pengetahuan tentang demam berdarah dengue: Systematic review - Zaki Surya Abdurrahman (Nur Science Institute, 2024)
Dengue Hemorrhagic Fever (DHF) remains a public health problem that requires effective education, and video media is considered capable of increasing public understanding by delivering more engaging, easy-to-understand audiovisual information. This study aims to determine the effectiveness of video media as a means of health education in increasing public knowledge regarding the prevention of Dengue Hemorrhagic Fever (DHF). The method used is a systematic literature review, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search was conducted across the ScienceDirect, ProQuest, Scopus, Sage Journals, Emerald, OneSearch, Garuda, RAMA, and Google Scholar databases, covering the period 2011–2021. Of the 1,503 articles identified, 15 met the inclusion criteria and were further analyzed using a Joanna Briggs Institute (JBI) review tool. The review results showed that health education using video media was more effective at increasing knowledge and behavior related to dengue prevention than conventional methods such as lectures. Audiovisual media help deliver health messages in a more interesting, concrete, and easily understood way for various community groups.